Researches of Pajauta Valley in Kernavė Leather Findings from Excavations of 1986 - Puškorius, Arūnas (Archaeologia Lituana, 2004)
While archaeological leather artefacts in Lithuania are not widely investigated thus far, some scientific works devoted to these findings provide interesting, valuable information. Leather, taken off the stabile archaeological environment, becomes a good place for various micro organisms to evolve, resulting in a further deterioration of leather. Archaeological leather artefacts can be carefully investigated only in laboratory, conserving material at the same time. For this reason full scientific information is usually presented later than a scientific excavation report. In 1986 irrigation engineering workers found remains of a wood road in Pajauta valley in Kernavė, to the SW of Castle hillfort. Archaeological excavations took place there, and a very rich cultural layer of the XIII–XIV c. Kernavė medieval town was discovered. Among the many findings, leather artefacts and remnants were found too. 77 pieces of leather remnants were examined. Leather of sheep (by number of single pieces – 27,3 %, by area – 42,4 %), cattle (53,2 % and 39,3 %), goat (5,2 % and 6,2 %), roe (5,2 % and 2,2 %), unidentified (9,1 % and 9,9 %) were found. This data cannot be compared to the other information of various periods from other places in Lithuania because of absence of any leather statistics. With reference to Gdansk artefacts of the X–XIV c., cattle leather predominates, goat, sheep and horse leather were less common, and pig leather was rare. Usually in European medieval towns, footwear comprises the majority of all leather artefacts in most archaeological excavations. Investigated leather remnants cannot be related to any particular homestead or trade, because these remnants were no more than casual waste. The data should be treated as comparative information, such as what kind of leather in the XIII–XIV c. was relatively more popular in Kernavė. In stitching holes some pieces of very deteriorated thread was found. It appeared to be a Z-spun cellulose fibre. Linen and hemp shoethreads were very popular in all of medieval Europe of this period. We have no information about curriers in Kernavė of the XIII–XIV c. With reference to laboratory analyses, vegetable and composite vegetable-alum tanning was identified. The latter tanning method was much better than the vegetable one, and provided superior quality, light-coloured leather. A few informative artefacts are discussed in this article: 3 fragments of soles, patched fragment of an unknown artefact, a single patch and a piece of ankle shoe upper. The sole of the right foot (270 x 115 mm) is worn away. The kind of animal was not identified. On the edges of the sole are the marks of a closed seam. On the front side of the sole is a former vamp place (Fig. 1). The leather profiled sole (170 x 73 mm) of an infant shoe has two vamps. The sole is 1.2 mm thick. The kind of animal was not identified. The sole was seamed together with upper only once, and no signs of making over were observed. Two 1.2 mm thick vamps in front and back part were seamed to the sole with S-spun strip made of cattle leather. Sheep leather was used for vamp b. The infant shoe had a one layer sole. When holes frayed, the footwear was repaired, but not by a professional master (Fig. 2:1). Remains of the front side sole (90 x 75 mm) with Z-spun leather strip. The strip was made of cattle leather (1.5 mm thick.) and animal hairs were observed on the surface (Fig. 2:2). Leather patch (92 x 33 mm) is seamed together with a fragment (39 x 41 mm) of unknown artefact. Both the strip (2.8 mm thick) and the patch (1.4 mm thick) are made of cattle leather. The fragment of unknown artefact is 1.1 mm thick and is made of goat lather (Fig. 2:3). The surface of the leather patch (61 x 82 mm) is very worn, and the animal was not identified. Only the signs of seaming with thread and leather strip on the edges were observed (Fig. 2:4). A fragment of upper (72 x 61 mm), probably of an ankle shoe, is made of 1.4 mm thick sheep leather. The ornament design is quite similar to other ankle shoes in Kernavė during this period, but upon observing the impresses on the surface of the leather using a microscope, the marks differed very much from those of embroidery. The upper may have been decorated with 1–2 mm diameter beads. Such beads were found in the nearby Kernavė-Kriveikiškės cemetery of the same period (Fig. 3). For the shoethread linden bass was used. Sometimes leather strips were used for the seaming too. This research shows that the professional craftsman of medieval Kernavė were capable of tanning leather very well and of making high quality shoes. Leather artefacts were very valuable. Both domestic and wild animal’s leather was use. To know the crafts of curriers and shoemakers in medieval Kernavė further research needs to be done.